N ‐(2‐aminoethyl) Acetamide Additive Enables Phase‐Pure and Stable α‐FAPbI3 for Efficient Self‐Powered Photodetectors - Cheng, Wenjie; He, Xiang; Wang, Jian‐Gan; Tian, Wei; Li, Liang (Advanced materials (Weinheim), 2022)
Formamidinium–lead triiodide (FAPbI3) perovskite is considered as one of the most promising perovskite materials for high‐performance photodetectors because of its narrow bandgap and superior thermal stability. Nevertheless, to realize efficient carrier transport and highly performing photodetectors, it imposes the requirement of fabricating α‐FAPbI3 with pure phase, preferred crystal orientation, large grain size, and passivated interface, which still remains challenging. Here, a facile strategy based on additive engineering to obtain pure‐phase FAPbI3 perovskite films by introducing N‐(2‐aminoethyl) acetamide into perovskite precursors is reported. The formation of chemical bond and hydrogen bond between N‐(2‐aminoethyl) acetamide and perovskite reduces the potential barrier in the phase‐transition process from an intermediate yellow phase to a final black phase, passivates the defects of the film, and leads to a high‐quality and phase‐pure α‐FAPbI3 perovskite. A self‐powered photodetector based on the as‐fabricated FAPbI3 film exhibits a maximum responsivity of 0.48 A W−1 at 700 nm with a peak external quantum efficiency of 95% at 440 nm. Moreover, the optimized device remains 83% of the initial performance after 576 h storage at ambient condition. This work provides a simple and feasible scheme for the preparation of high‐quality phase‐pure α‐FAPbI3 perovskite and associated devices. A facile strategy to obtain phase‐pure α‐FAPbI3 perovskite films by introducing N‐(2‐aminoethyl) acetamide into perovskite precursors is reported. The additive reduces the potential barrier in the phase transition process, passivates the defects of the film, and leads to a high‐quality and phase‐pure α‐FAPbI3 perovskite. The resultant self‐powered photodetector based on the as‐fabricated FAPbI3 film exhibits superior performance.